Moderating Influence That Islamic Law Intensity Of Causal Relationship Between Regional Economic Growth And Determinant: Study Empiricalon District / City In The Province Nanggroe Aceh Darussalam (Nad) - Safriadi M Yunus AKS; Dharma Tintri Ediraras; Toto Sugiharto (Publisher Cv. Inara, 2021)
Policy of the Government of the Republic of Indonesia to grant special autonomy to the Provincial Government of Nangroe Aceh Darussalam (NAD) through the concept of asymmetric decentralization accompanied by the issuance of a law on the implementation of Islamic Sharia in a kaffah manner, opening opportunities for the government and the people of NAD Province to increase the pace of development economy based on faith and piety to Allah SWT. How the impact of the implementation of these policies on regional economic growth in the Province of NAD has not been widely studied. The purpose of this dissertation is to analyze the causal relationship between regional economic growth and its determinants and to analyze the moderating role of the intensity of the application of Islamic law on the causal relationship. The target population is districts/cities in NAD Province and the sample consists of 23 units of analysis (5 cities and 18 districts). Secondary data on a ratio scale to measure research variables, namely HDI, technology investment, population, regional development expenditure, intensity of the application of Islamic Sharia, and regional economic growth for the 2010 - 2019 period, sourced from the Central Statistics Agency and the Regional Office of the Ministry of Religion of NAD Province. The data analysis technique used descriptive statistics and panel data regression analysis to test 10 research hypotheses. The results show that simultaneously capital, HDI, technology investment, population, and regional development expenditures have a very large influence on regional economic growth in NAD Province. Partially, capital, technology investment, population, and regional development expenditure are the determinants of regional economic growth in NAD Province. The four determinant variables have an effect on increasing regional economic growth. Regencies/cities that have large capital, moderate and innovative technology investment accompanied by a high population, and are supported by adequate regional development expenditures, have an impact on high economic growth in NAD Province. The intensity of the application of Islamic law moderates the causal relationship between capital, technology investment and population on regional economic growth, while the intensity of the application of Islamic law has not shown a significant role in moderating the causal relationship between the human development index and regional development expenditures on regional economic growth. This indicates that the intensity of the application of Islamic Sharia in the province of Aceh has given a significant role to all sectors in increasing regional economic growth. further research is suggested to use Economic Well Being Theory and include fiscal and regional retribution variables, education and ICT readiness index and electronic-based service system index.